Arthropod management in vineyards: pests, approaches, and future directions - Vincent, Charles; Isaacs, Rufus; Bostanian, Noubar J. (Springer Netherlands, 2012)
In recent decades, viticulture has undergone a tremendous growth worldwide. Vineyard pest management is a dynamic and evolving field, and the contributed chapters in Arthropod Management in Vineyards: Pests, Approaches, and Future Directions provide insights on the management of insects and mites that limit this important crop and its products. It provides a state-of-the-science overview of insects and mites affecting grape production around the world. Written by international experts from the major grape-growing regions, it provides a global overview of insects/mites affecting vines and the novel strategies being used and in development to prevent economic losses, including  invasive pests affecting viticulture. The book contains reviews of the theoretical basis of integrated pest management, several chapters on biological control, mode of action of pesticides along with the current status of chemical control, as well as in-depth and well-illustrated reviews of the major insect/mite pests affecting grape production and how they are being managed in different grape growing regions in five continents. This text will serve as a primary resource for applied entomologists, students, growers, and consultants with interests in the intersection of viticulture and applied entomology.